Association of sleep characteristics with atrial fibrillation: the Multi-Ethnic Study of Atherosclerosis. Issue 9 (18th May 2015) - Kwon, Younghoon; Gharib, Sina A; Biggs, Mary L; Jacobs, David R; Alonso, Alvaro; Duprez, Daniel; Lima, Joao; Lin, Gen-Min; Soliman, Elsayed Z; Mehra, Reena; Redline, Susan; Heckbert, Susan R
Abstract : Background: Population-based studies have linked measures of sleep disordered breathing to nocturnally occurring atrial fibrillation (AF) episodes. Whether measures of sleep disordered breathing and sleep quality are associated with prevalent AF has not been studied in an unselected population. We investigated the cross-sectional association with prevalent AF of objectively collected prespecified measures of overnight sleep breathing disturbances, sleep stage distributions, arousal and sleep duration. Methods: AF prevalence, defined by diagnosis codes, study electrocardiography and sleep study were examined among Multi-Ethnic Study of Atherosclerosis (MESA) participants who underwent polysomnography in the MESA Sleep Study (n=2048). Measurements and main results: Higher apnoea hypopnoea index (AHI) was associated with increased odds of AF, although the significance was attenuated after full adjustment for covariates including prevalent cardiovascular disease (OR: 1.22 (0.99 to 1.49) per SD (17/h), p=0.06). Analyses of sleep architecture measures and AF revealed significantly lower odds of AF associated with longer duration of slow wave sleep (OR: 0.66 (0.5 to 0.89) per SD (34 min), p=0.01) which persisted after additionally adjusting for AHI (OR: 0.68 (0.51 to 0.92), p=0.01). Higher sleep efficiency was significantly associated with lower likelihood of AF but the significance was lost when adjusted for AHI. No significant association was present between sleep duration and AF. In a model including AHI and arousal index, the association between AHI and AF was strengthened (AHI: OR 1.49 (1.15 to 1.91) per SD, p=0.002) and a significant inverse association between arousal index and AF was observed (OR 0.65 (0.50 to 0.86) per SD (12/h), p=0.005). Conclusions: In a study of a large multiethnic population, AF was associated with AHI severity, and was more common in individuals with poor sleep quality as measured by reduced slow wave sleep time, a finding that was independent of AHI.